Village Community Empowerment Model in Smart Village Perspective (Study on Village Communities in Jombang Regency) - Muzaqi, Ajie Hanif; Tyasotyaningarum, Berlian (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2022)
Along with the ability of the community and government to manage their area, currently the focus of development is not only on cities/districts but moving towards rural areas. One of the development concepts that can be used is the smart village.The concept of smart village empowerment is designed as an enabler of competitive, sustainable and inclusive village development.Therefore, this study aims to develop a smart village that can be applied to rural areas in Jombang Regency.The model-building method is used to reconstruct the conceptual model that is collided with the existing empirical conditions.The results of the study contained three basic dimensions of a smart village, namely smart government, smart people, and smart environment.These dimensions will produce a harmonious collaboration in a constructive and sustainable manner.In addition, to achieve the goal of collaboration, it is necessary to use technology and information (IT) so that the welfare and independence of the village community of Jombang Regency can be achieved.